Validation of control of allergic rhinitis and asthma test for children (CARATKids)--a prospective multicenter study - Linhares, DV (2014)
BACKGROUND: Control of Allergic Rhinitis and Asthma Test for Children (CARATKids) is the first questionnaire that assesses simultaneously allergic rhinitis and asthma control in children. It was recently developed, but redundancy of questions and its psychometric properties were not assessed. This study aimed to (i) establish the final version of the CARATKids questionnaire and (ii) evaluate its reliability, responsiveness, cross-sectional validity, and longitudinal validity. METHODS: A prospective observational study was conducted in 11 Portuguese centers. During two visits separated by 6 wk, CARATKids, visual analog scale scales and childhood asthma control test were completed, and participant's asthma and rhinitis were evaluated by his/her physician without knowing the questionnaires' results. Data-driven item reduction was conducted, and internal consistency, responsiveness analysis, and associations with external measures of disease status were assessed. RESULTS: Of the 113 children included, 101 completed both visits. After item reduction, the final version of the questionnaire has 13 items, eight to be answered by the child and five by the caregiver. Its Cronbach's alpha was 0.80, the Guyatt's responsiveness index was -1.51, and a significant (p < 0.001) within-patient change of CARATKids score in clinical unstable patients was observed. Regarding cross-sectional validity, correlation coefficients of CARATKids with the external measures of control were between 0.45 and -0.69 and met the a priori predictions. In the longitudinal validity assessment, the correlation coefficients between the score changes of CARATKids and those of external measures of control ranged from 0.34 to 0.46.